Virus-Infected Plants Altered the Host Selection of Encarsia formosa, a Parasitoid of Whiteflies - Liu, Xin; Chen, Gong; Zhang, Youjun; Xie, Wen; Wu, Qingjun; Wang, Shaoli (Frontiers in Physiology, 2017)
The sweetpotato whitefly Bemisia tabaci (Gennadius) is one of the most invasive pest species worldwide. Q and B biotypes are the two most devastating species within the B. tabaci complex. Bemisia tabaci can vector hundreds of plant viruses that seriously threaten crop production. Endoparasitoid, Encarsia formosa Gahan, is widely used to control whiteflies, however, little is known about the effects of virus-infected plants on E. formosa parasitism of B. tabaci. Here, we reported that tomato, which was infected with Tomato Yellow Leaf Curl Virus (TYLCV), altered the host selection of E. formosa between B. tabaci Q and B biotypes. On healthy tomato plants, parasitism and host selection by E. formosa did not differ between the 3rd-instar nymphs of B. tabaci Q and B biotypes. On TYLCV-infected tomato plants, however, B. tabaci Q biotype were significantly more attractive to E. formosa than B biotype. When TYLCV-infected tomato plants were infested with B. tabaci Q or B biotype, volatile profiles differed quantitatively but not qualitatively. Olfactometer assays suggested that the preference of E. formosa to Q over B biotype was associated with an elevated level of β-Myrcene, β-Ocimene, β-Caryophyllene, and α-Humulene from TYLCV-infected tomato plants. Key Words: Encarsia formosa, Bemisia tabaci, Tomato Yellow Leaf Curl Virus, Host selection, Plant volatiles